(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2026)
Background: Renal impairment is common in Coronavirus Disease-2019 (COVID-19) and the impact of renal impairment on patient outcomes may differ due to geographical area, differences in healthcare systems or hospital capacities. This study investigated the factors associated with in-hospital and 90 days outcomes in COVID-19 patients who needed hemodialysis for their renal impairment in a public tertiary hospital in Bangladesh. Materials and methods: This prospective observational study was conducted in Chittagong Medical College Hospital (CMCH) Chattogram, Bangladesh. Consecutive COVID-19 patients (Both confirmed and suspected) with renal impairment and subjected to hemodialysis were included. The demographic characteristics, clinical course and laboratory parameters were recorded. Outcome measures were in-hospital and 90 days mortality. Results: 315 patients were included in the study and 301 patients completed the 90 days follow up. The in-hospital mortality rate was 29.8% and 90 days mortality rate was 31.2%. Age was significantly higher in patients who died in hospital (47.5±14.3 vs 51.6±16.3 years, p=0.028) and died within 90 days (44.5±14.0 vs 50.9±3.2 years, p=0.002) of admission than who survived. Mortality in patients with End Stage Renal Disease (ESRD) on Maintenance Hemodialysis (MHD) were less than AKI and CKD patients (p=0.007) regarding in-hospital outcome. Total WBC count was also higher in expired patients both in-hospital (p=0.023) and 90 days (p=0.031) than survived patients. Median blood urea (188.0 vs 210.0 mg/dL) SGPT (31.0 vs 36.0 U/L) and D-dimer (2.6 vs 4.6 ug/mL) were significantly higher and Lymphocyte count was significantly lower in expired group than survived group regarding in-hospital mortality (p<0.05). There was no significant difference of serum creatinine, CRP, serum ferritin between expired and survived groups. Conclusions: This study showed that patients with COVID-19 who required hemodialysis were higher mortality rate both in-hospital and 90 days follow up. Older age, leukocytosis, lymphopenia, uremia, increased SGPT and D-dimer were predictors of in-hospital mortality. ESRD on MHD had good outcome. Older age and leukocytosis were predictors of 90 days mortality. JCMCTA 2025 ; 36 (2) : 85-91